2009
DOI: 10.1167/iovs.08-2815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pirfenidone on Proliferation, Migration, and Collagen Contraction of Human Tenon’s Fibroblasts In Vitro

Abstract: These findings indicate that pirfenidone inhibits proliferation, migration, and collagen contraction of HTFs at nontoxic concentrations. A decrease in autocrine TGF-beta signaling may have a role in the effects of pirfenidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 24 publications
10
75
0
4
Order By: Relevance
“…In agreement with in vivo model data, in vitro antiproliferative effects of PFD were also confirmed with human leiomyoma cells [10], human Tenon fibroblasts [11], and rat cardiac fibroblasts [12]. Notably, Lin et al [11] have reported that PFD suppressed cell proliferation of human Tenon fibroblasts by inducing G0/G1 cell cycle arrest. Other reports have demonstrated antiproliferative effects of PFD in cancer-associated fibroblasts derived from human lung cancer patients [13] and myofibroblast-like pancreatic stellate cells (PSCs) derived from human pancreatic cancer patients [14].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In agreement with in vivo model data, in vitro antiproliferative effects of PFD were also confirmed with human leiomyoma cells [10], human Tenon fibroblasts [11], and rat cardiac fibroblasts [12]. Notably, Lin et al [11] have reported that PFD suppressed cell proliferation of human Tenon fibroblasts by inducing G0/G1 cell cycle arrest. Other reports have demonstrated antiproliferative effects of PFD in cancer-associated fibroblasts derived from human lung cancer patients [13] and myofibroblast-like pancreatic stellate cells (PSCs) derived from human pancreatic cancer patients [14].…”
Section: Introductionsupporting
confidence: 76%
“…Specifically, PFD was shown to be effective in various in vivo models including a rat model of myocardial infarction [5,6], a mouse model of pulmonary fibrosis [7], a mouse model of nonalcoholic steatohepatitis [8], and a rats model of renal fibrosis [9]. In agreement with in vivo model data, in vitro antiproliferative effects of PFD were also confirmed with human leiomyoma cells [10], human Tenon fibroblasts [11], and rat cardiac fibroblasts [12]. Notably, Lin et al [11] have reported that PFD suppressed cell proliferation of human Tenon fibroblasts by inducing G0/G1 cell cycle arrest.…”
Section: Introductionmentioning
confidence: 56%
“…26 Controlling the balance of fibroblasts and myofibroblasts is thought to be critical in postoperative healing. Clinical studies observed increased levels of TGF-b in both conjunctival tissue and aqueous humor of postfiltration surgery patients, 26,27 which might stimulate the proliferation and migration capacity of HTFs in vivo, resulting surgical failure. Transforming growth factor-b2 is recognized as the predominant isoform of all three isoforms in humans and is implicated in the pathogenesis of several ocular fibrosis diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro antifibrotic activities of pirfenidone (table 3) fall into three general categories: reduction of fibroblast and myofibroblast proliferation [79,[84][85][86], inhibition of extracellular matrix synthesis/deposition [79][80][81][82][83]86], and reductions in fibrotic markers [81,82,84,85]. Each of these activities is relevant to the attenuation of chronic fibrosis, is consistent with the effects reported for pirfenidone in animal models, and may be relevant to the use of pirfenidone in the treatment of IPF.…”
Section: Effects In Cell-based Assaysmentioning
confidence: 99%